Epithelial and mesenchymal prostate cancer cell population dynamics on a complex drug landscape. (30th August 2017) - Lin, Ke-Chih; Torga, Gonzalo; Wu, Amy; Rabinowitz, Joshua D; Murray, Wesley J; Sturm, James C; Pienta, Kenneth J; Austin, Robert
Abstract: We have improved our microfluidic cell culture device that generates an in vitro landscape of stress heterogeneity. We now can do continuous observations of different cancer cell lines and carry out downstream analysis of cell phenotype as a function of position on the stress landscape. We use this technology to probe adaption and evolution dynamics in prostate cancer cell metapopulations under a stress landscape of a chemotherapeutic drug (docetaxel). The utility of this approach is highlighted by analysis of heterogenous prostate cancer cell motility changes as a function of position in the stress landscape. Because the technology presented here is easily adapted to a standard epifluorescence microscope it has the potential for broad application in preclinical drug development and assays of likely drug efficacy.